2014
DOI: 10.1095/biolreprod.114.124636
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Body Weight Gain During the Juvenile Period Alters Neuropeptide Y-Gonadotropin-Releasing Hormone Circuitry in Prepubertal Heifers

Abstract: Increased body weight (BW) gain during the juvenile period leads to early maturation of the reproductive neuroendocrine system. We investigated whether a nutritional regimen that advances the onset of puberty leads to alterations in the hypothalamic neuropeptide Y (NPY) circuitry that are permissive for enhanced gonadotropin-releasing hormone (GnRH) secretion. It was hypothesized that NPY mRNA and NPY projections to GnRH and kisspeptin neurons are reduced in heifers that gain BW at an accelerated rate, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 72 publications
4
34
1
9
Order By: Relevance
“…The reproductive neuroendocrine postnatal system accelerates puberty during earlier calfhood, from 3 to 4.5 months of age, which might be facilitated by early programming of leptin secretion in adipose tissue during juvenile development using a stair-step nutritional regimen (Cardoso et al, 2014). Recently, Alves et al (2015) described that the reduction in neuropeptide-Y innervation of gonadotropin-releasing hormone neurons occurs in response to elevated body weight gain during the juvenile period. Nelore crossbred heifers had a higher heterozygosity, possibly due to a better adaptation to reach earlier puberty as described by Monteiro et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive neuroendocrine postnatal system accelerates puberty during earlier calfhood, from 3 to 4.5 months of age, which might be facilitated by early programming of leptin secretion in adipose tissue during juvenile development using a stair-step nutritional regimen (Cardoso et al, 2014). Recently, Alves et al (2015) described that the reduction in neuropeptide-Y innervation of gonadotropin-releasing hormone neurons occurs in response to elevated body weight gain during the juvenile period. Nelore crossbred heifers had a higher heterozygosity, possibly due to a better adaptation to reach earlier puberty as described by Monteiro et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Others studies found that the onset of puberty is related to growth rate and the amount of body fat (Nogueira, 2004). In a recent study, heifers were weaned at approximately 4 month of age and fed diets to promote relatively low (0.5 kg/day) or high (1.0 kg/day) rates of body weight gain until 8.5 month of age (Alves et al, 2015). Heifers that gained body weight at a greater rate exhibited greater circulating concentrations of leptin and reduced overall NPY expression in the arcuate nucleus.…”
Section: Hasten Of Reproductive Age Of Nelore Heifersmentioning
confidence: 99%
“…Heifers that gained body weight at a greater rate exhibited greater circulating concentrations of leptin and reduced overall NPY expression in the arcuate nucleus. The authors suggest that such changes may mediate the nutritional programming of the reproductive neuroendocrine axis and facilitate an early onset of puberty in heifers (Alves et al, 2015).…”
Section: Hasten Of Reproductive Age Of Nelore Heifersmentioning
confidence: 99%
“…Many experiments have been conducted to quantify the requirements of energy, protein, and minerals of pregnant animals (Bell et al, 2005;Ferrell, 1991;Ferrell et al, 1976) and the impact of early calfhood nutrition on their reproductive development (Allen et al, 2012;Alves et al, 2015;Amstalden et al, 2014;Cardoso et al, 2014a;Cardoso et al, 2014b). However, not until recently have scientists inquired about controlling the type and quality of the nutrition during fetus development and its long-lasting impacts on the growth and development of the newborn through adulthood: the fetal programming theory.…”
Section: Early Nutritional Fetal Programmingmentioning
confidence: 99%